Dukungan sosial dan kecenderungan kecanduan media sosial pada Gen Z (SUKMA : Jurnal Penelitian Psikologi, 2023)
It is well-recognized that social media addiction tendencies are linked to the excessive usage of social media which causes disruptions in daily activities. This current study aims to examine the correlation between social support and the tendency towards social media addiction in Generation Z. This study uses a correlational and data were obtained using on the basis of the social support scale and social media addiction tendency scale. The population utilized in this study comprises individuals from Gen Z residing in Surabaya, with a total of 88 participants between the ages of 18-24 years old who actively engage with more than one social media platforms. The data analysis technique used is product moment correlation. The study reveals that social support holds a substantial negative association with the propensity for social media addiction among Gen Z. Accordingly, the enhancement of social support among Gen Z may serve as an approach to minimize the tendency towards social media addiction. Kecenderungan kecanduan media sosial diketahui memiliki hubungan dengan penggunaan media sosial yang berlebihan, sehingga mengganggu aktivitas seharihari. Penelitian ini bertujuan untuk menguji hubungan antara dukungan sosial dengan kecenderungan kecanduan media sosial pada Gen Z. Penelitian ini menggunakan metode kuantitatif korelasional dan data dikumpulkan menggunakan skala dukungan social dan skala kecenderungan kecanduan media sosial. Partisipan dalam penelitian ini adalah Gen Z yang ada di Surabaya, dengan 88 partisipan berusia 18-24 tahun yang menggunakan media sosial aktif lebih dari satu. Teknik analisis data yang digunakan adalah korelasi product moment. Penelitian ini menunjukkan terdapat hubungan negatif yang sangat signifikan antara dukungan sosial dengan kecenderungan kecanduan media sosial pada Gen Z. Oleh karena itu, peningkatan dukungan sosial pada Gen Z dapat menjadi cara untuk mencegah kecenderungan kecanduan media sosial.